TORAKOCHIRURGIAResection of a hypernephroma involving the IVC: a safe algorithm - Parissis, Harry; Blach, Andrzej; Krawczyk, Arkadiusz; Walsh, Kevin; Veeresingam, Dave; DaCosta, Mark (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Objectives: To report a stepwise approach for the successful resection of a complex pathology: renal cell carcinoma invading the IVC into a variable length (level I-IV extension). Methods: An algorithm of the plan of action, according to the level of extension of the tumour, is presented. Results: MRI is needed to determine the extent of IVC involvement. Perioperative TOE is useful to quantify the adherence, cephalad extension and mobility of the tumour. A team approach of anaesthetists/urologists is necessary. Start with mobilization of the affected kidney. No irrevocable steps until resection guaranteed. Mobilization of infra- and supra-hepatic IVC. For level I-II disease: use intermittent caval clamp, and cell saver. For level III: institute CPB (venous cannulae: SVC, right femoral vein). Control of the cavo-atrial junction. Use Pringle manoeuvre and prepare to briefly cross-clamp the supra-celiac abdominal aorta if necessary. Right atrium can be opened and tumour mobilized from above and below and simultaneously pushed and drawn down and extracted. For level IV or suspected suboptimal thrombectomy for level III disease use a brief period of total circulatory arrest (TCA). Repair the cavotomy with a pericardial patch. Conclusions: Success of IVC surgery depends on careful patient selection and attention to detail. Total clearance of the IVC from a well adherent tumour (using endarterectomy technique and a bloodless field) is probably the single most important factor for prognosis.